2016
DOI: 10.17113/ftb.54.03.16.4519
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evaluation of Phenylalanine Ammonia Lyase (PAL) from Endemic Cyathobasis fruticulosa (Bunge) Aellen. for the Dietary Treatment of Phenylketonuria (PKU)

Abstract: SummaryEnzyme substitution therapy with the phenylalanine ammonia lyase (PAL) is a new approach to the treatment of patients with phenylketonuria (PKU). This enzyme is responsible for the conversion of phenylalanine to trans-cinnamic acid. We assessed the PAL enzyme of the endemic plant Cyathobasis fruticulosa (Bunge) Aellen. for its possible role in the dietary treatment of PKU. The enzyme was found to have a high activity of (64.9±0.1) U/ mg, with the optimum pH, temperature and buff er (Tris-HCl and l-pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
(46 reference statements)
0
10
0
1
Order By: Relevance
“…In addition, the phenylpropanoid pathway is responsible for the biosynthesis of lignin, flavonoids and benzenoids etc., which all play a role in protecting the plant against biotic and abiotic stress [48,49]. Trans-cinnamic acid acts as a mediator during the catalytic process of phenylalanine to secondary metabolites such as lignin, which indicates its key function in the phenylpropanoid biosynthesis pathway [50]. In the present study, trans-cinnamic acid that acts as a precursor of many secondary substances was up-regulated in the T1 vs Cd comparison, but was down-regulated in the T2 vs Cd comparison.…”
Section: Secondary Metabolites To Chelate and Sequestrate Cadmiummentioning
confidence: 99%
“…In addition, the phenylpropanoid pathway is responsible for the biosynthesis of lignin, flavonoids and benzenoids etc., which all play a role in protecting the plant against biotic and abiotic stress [48,49]. Trans-cinnamic acid acts as a mediator during the catalytic process of phenylalanine to secondary metabolites such as lignin, which indicates its key function in the phenylpropanoid biosynthesis pathway [50]. In the present study, trans-cinnamic acid that acts as a precursor of many secondary substances was up-regulated in the T1 vs Cd comparison, but was down-regulated in the T2 vs Cd comparison.…”
Section: Secondary Metabolites To Chelate and Sequestrate Cadmiummentioning
confidence: 99%
“…The work [ 26 ] presents the results of studies of the accumulation of tyrosine, phenols, and cinnamic acid in the medium at enzyme activity 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, and 8.0 U/mg during incubation for 1, 2, 4, and 8 h. It was found that the concentrations of tyrosine, phenols, and cinnamic acid were the highest at the activity of l -phenylalanine ammonia-lyase 5.0 U/mg after incubation for 4 h. In [ 27 ], the PAL activity in relation to the accumulation of trans-cinnamic acid, tyrosine, flavonoids, benzoids, and phenolic glycosides was studied. The results obtained in [ 27 ] are in good agreement with the data obtained in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the phenylpropanoid pathway is responsible for the biosynthesis of lignin, avonoids and benzenoids etc., which all play a role in protecting the plant against biotic and abiotic stress [55,56]. Trans-cinnamic acid acts as a mediator during the catalytic process of phenylalanine to secondary metabolites such as lignin, which indicates its key function in the phenylpropanoid biosynthesis pathway [57]. In the present study, trans-cinnamic acid that acts as a precursor of many secondary substances was up-regulated in the T1 vs Cd comparison, but was down-regulated in the T2 vs Cd comparison.…”
Section: Secondary Metabolites To Chelate and Sequestrate Cadmiummentioning
confidence: 99%